First ground-based observations of mesopause temperatures above the Eastern-Mediterranean Part I: Multi-day oscillations and tides. (March 2017) - Silber, Israel; Price, Colin; Schmidt, Carsten; Wüst, Sabine; Bittner, Michael; Pecora, Emilio
Abstract: The mesopause region (~90 km altitude) is the coldest region of our atmosphere, and is found at the boundary between the upper mesosphere and lower thermosphere. Ground-based spectrometers, which are sensitive to the emissions from the hydroxyl (OH * ) airglow layer (lying at ~87 km altitude), are used to monitor the temperature variability within the mesosphere-lower-thermosphere (MLT), at high temporal resolution. The variability of the MLT region of the atmosphere is driven by momentum deposition from gravity waves, atmospheric tides and planetary waves. The displacement of air caused by these waves can produce strong temperature, wind and species concentration perturbations. In this study we present an analysis of 4-years of OH * rotational temperature data, acquired with the German Aerospace Center (DLR) GRIPS-10 (Ground Based Infrared P-branch Spectrometer) instrument, which was installed in Israel in November 2011. This instrument provided the first long-term ground-based observations of airglow emissions in the Eastern Mediterranean. We show the nocturnal mean temperature analysis, which includes time series as well as spectral analysis of the data. In addition, we obtain (migrating) tidal oscillation estimates from the high resolution (1 min) data, by using harmonic fitting, and we analyze the variability of planetary wave signatures in the residual temperature data, which are retrieved after the removal of the tidal harmonic fits from the data. In this analysis of the residual data we find a dominant quasi-5–7 day planetary wave influence on the mesopause temperatures above the Eastern Mediterranean. Highlights: The first ground-based observations of mesopause temperature in the Eastern Mediterranean region are presented. Tidal oscillation estimates (from 1 min resolution data) and their variability in the nighttime mesopause temperatures are obtained. Analysis of planetary wave signatures in the nighttime temperatures shows a dominant quasi-5–7 day planetary wave influence.